Multistage Gold-Polymetallic Mineralization in the Bou Azzer District, Anti-Atlas, Morocco: Insights from Ore Microscopic, Geochemical, and Fluid Inclusion Studies - Amina Wafik; Basem Zoheir; Fouad Benchekroun; Rachid Benaouda; Mohamed Ben Massoude; Youssef Atif; Amin Beiranvand Pour; Shojaeddin Niroomand; Amal El Arbaoui; Abdelhak Karfal; Lhou Maacha (Geofluids)
The Bou Azzer polymetallic Co-Ni-As±Au±Ag veins in the Central Anti-Atlas (Morocco) are significant sulfide ores hosted by Neoproterozoic ophiolites and are associated with felsic intrusive and subvolcanic phases. We report new mineralogical and fluid inclusion data to better understand mineralization’s formation processes and fluid evolution which are analyzed and merged with the existing published data. Gold-bearing sulfide-arsenide-quartz (±carbonate) veins in Bou Azzer exhibit mineralogical and fluid inclusion features similar to the epithermal and porphyry-style gold deposits. Modeling of widespread primary and pseudosecondary saline aqueous inclusions in the mineralized quartz veins suggests that circulating metalliferous brines, with estimated temperatures of ~275°C and pressures<550 bars and salinity<40%, precipitated sulfides in the veins. Gold was most likely transported as bisulfide complexes, and ore deposition was controlled by fluctuations in oxygen fugacity (ƒO2) upon fluid cooling. The systematic decrease in temperatures and salinities from an early prearsenide stage to a late paragenetic arsenide and sulfide stage was likely linked with extensive mixing with meteoric waters in a shallow hydrothermal environment. Available sulfur, oxygen, and hydrogen stable isotope data for the Bou Azzer sulfide-arsenide-quartz veins indicate variable fluid sources, primarily magmatic and metamorphic fluids. The wide range of the estimated mineralization ages (from 680 Ma to 210 Ma) and the spatial association with major shear zones and felsic intrusive stocks imply a significant role of the regional tectonic activities or reflect complex and superimposed mineralization episodes, corresponding to orogenic events spanned the Pan-African cycle to the Atlasic orogenesis.